Edukasi Media Video dan Booklet terhadap Motivasi dan Sikap Orangtua dalam Merawat Balita dengan Gastroenteritis - Padila Padila; Juli Andri; Muhammad Bagus Andrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of providing education using video media and booklets on the motivation and attitudes of parents in caring for toddlers with gastroenteritis. This type of research is a quasi-experimental design with a non-pretest-posttest design. The study's results found a difference in the average score of parents' motivation and attitudes in caring for toddlers with gastroenteritis before and after providing education. In the video media group ρ motivational value (0.01) and perspective (0.00), in the booklet media group with ρ motivational value (0.02) and attitude (0.00), and the video media and booklet combination group with ρ motivational value (0.00) and perspective (0.00). In conclusion, there is a significant effect of the use of educational media on increasing the average score of parents' motivation and attitudes in caring for toddlers with gastroenteritis. The combination of education using video media and booklets gave more effective results than other educational groups. Keywords: Booklet, Video Media, Motivation, Health Education, Attitude